Reviving Germany's wealth tax creates high revenue potential - Stefan Bach; Andreas Thiemann (DIW Economic Bulletin, 2016)
Compared to the rest of Europe, Germany exhibits an especially high concentration of wealth. According to estimates based on a microsimulation model, a German wealth tax could generate an estimated ten to 20 billion euros per year in revenue-even with high tax allowances-and slightly reduce the inequality of income distribution, as well. Collection costs would range from four to eight percent in relation to the tax revenue, and would thus be comparable to the collection costs for income and corporate taxes. However, it is possible that the tax revenue could be noticeably diminished as a result of tax avoidance.
Keywords: H24; D31; H31; 330; wealth tax; wealth distribution